Relationship between internal load indicators and changes on intermittent performance after the preseason in professional soccer players - Campos-Vazquez, M. A.; Toscano-Bendala, F. J.; Mora-Ferrera, J. C.; Suarez-Arrones, L. J. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to examine the effects of accumulated internal training load (ITL) during the preseason (4 weeks) on changes in the intermittent performance, in a professional soccer team. Twelve professionals soccer players (Mean ± SD age: 27.7 ± 4.3 years; height: 177.1 ± 6.2 cm; body mass: 73.1 ± 5.2 kg; % body fat [Faulkner]: 10.2 ± 1.2) belonging to a Spanish second division team (2013-2014) participated in this study. The 30-15 intermittent fitness test was performed before and after the preseason, and the speed for the last period completed by each player was recorded (VIFT). During the preseason, the team alternated practice of training sessions (TRNs) with friendly matches (FMs). Session rating of perceived exertion (sRPE), heart rate (HR), and HR reserve were analyzed every TRN and FM to calculate ITL (ITL: sRPE-TL, Edward's-TL and Edward's-TLres). The players' VIFT substantially increased after the preseason period (20.1 ± 0.8 vs. 21.1 ± 0.8 km/h; effect size [ES] = 1.15 ± 0.25; almost certainly). The average value of sRPE throughout FMs was substantially greater than the value of the TRNs (7.4 ± 0.9 vs. 5.25 ± 0.2; ES = 2.31 ± 2.45; almost certainly). sRPE-TL, practice volume, and sum of RPE during the preseason were positively and largely correlated (r = 0.70-0.75) with changes on intermittent performance. No relationships were found between HR-derived measures of exercise load and changes on intermittent fitness. The present results suggest that practice volume and subjective measures of TL, related better than HR-based TL methods to changes on intermittent performance after the preseason, in professional soccer players.